Effects of aerobic physical activity to cardio-respiratory fitness of the elderly population: systematic overview - Nikola Aksović; Bjelica Bjelica; Marko Joksimović; Iryna Skrypchenko; Siniša Filipović; Filip Milanović; Bojan Pavlović; Bojan Ćorluka; Radomir Pržulj (IP Iermakov S.S., 2020)
Background and Study Aim. Aerobic training is effective manner of exercising aimed at improving cardio-respiratory fitness of young people. However, its effects to the elderly population (over the age of 60), depending on characteristics of the participant (gender, health status, lifestyle, etc.), is still unclear. Aim of this research is systematic overview of the available literature dealing with the topic of effects of aerobic training to cardio-respiratory fitness of the elderly population over the age of 60, depending of gender (male/female), BMI (overweight/normal weight), lifestyle (active/sedentary), health status (diabetes/hypertension/metabolic syndrome). Material and methods: Total number of papers with published research results which met the criteria was 32. Walking is effective manner of exercising which influences improvement of maximum oxygen consumption (mean value: ±SD:12.91±7.40%). Introduction of activities with greater impact (bicycle and jogging) provides more effect to the cardio-respiratory fitness (mean value: ±SD:14.28±7.48%). Results: Aerobic training intensity level (moderate vs. high) makes no significant difference to the adaptive response of the cardio-respiratory fitness in elderly population. Training in duration of 6 weeks may significantly influence increase in maximum oxygen consumption, but longer training duration, however, has better effect.  Endurance training has similar effects to improvement of cardio-respiratory fitness in both men and women. On the other hand, it seems that active people have lower adaptive response in comparison to sedentary people (8.3% vs. 18.84%). Effect is similar between overweight and normal weight participants (18.48% vs. 8.6%). Positive influence of aerobic training was also observed in participants with hypertension, metabolic system and diabetes type 2. Conclusion: Results clearly suggest benefits of aerobic training on cardio-respiratory fitness of elderly population. The effect may, however, vary depending of duration, type of activity, as well as characteristics of the sample.